Genetic typing of equine arteritis virus isolates from Argentina - Echeverría, María Gabriela (2007)
We report the nucleotide sequence and genetic diversity of four Equine Arteritis Virus (EAV) ORF 5 and 6 from Argentina isolates, obtained from asymptomatic virus-shedding stallions. Nucleic acid recovered from the isolates were amplified by RT-PCR and sequenced. Nucleotide and deduced amino acid sequences from the Argentine isolates were compared with 17 sequences available from the GenBank. Phylogenetic analysis revealed that the Argentine isolates grouped together in a definite cluster near European strains. Despite the greater genetic variability among ORF 5 from different isolates and strains of EAV, phylogenetic trees based on ORF 5 and 6 are similar. Both trees showed that virus sequences from America and Europe segregate into distinct clades based on sequence analysis of either ORF 5 or 6. This study constitutes the first characterization of Argentine EAV isolates.